POSSIBILITIES TO IMPROVE THE EPIDEMIOLOGICAL RESEARCHES REGARDING THE ORAL HEALTH IN ROMANIAN N-E AREA - Murariu Alice; Dascalu Cristina; Edlibi Al Hage Walid (Romanian Dental Association for Education, 2019)
The application of effective strategies for implementing clinical and health services interventions is an issue that concerns many researchers and healthcare providers. An objective of an effective epidemiological research regarding the oral health must be the measuring of the socioeconomic, and systemic status factors, to establish correlations between the investigated factors and the oral health status. Also the epidemiological researches must be focused on recording the usual dental and periodontal indices as well as on finding sensible immunological predictors linked to periodontal disease, a chronic pathology that affects all age categories and is associated to many general diseases. The epidemiological studies performed in N-E areas of Romania can increase the knowledge of the oral health status and factors that influencing it, as well as will determine the correlations between these factors and the health status of the oral cavity. The results of epidemiological studies can help to establish clinical and paraclinical indicators in the establishment of an oral diagnosis with high predictability. The creation of a database to national and international level regarding oral health in Romanian N-E area, can conduct to the implementation of a new prevention programs in areas where the results of the epidemiological study will find a high prevalence of the oral diseases.